PENGARUH ATRIBUT PRODUK DAN VARIETY SEEKING TERHADAP KEPUTUSAN PERPINDAHAN MEREK HANDPHONE NOKIA KE SMARTPHONE SAMSUNG (Survei pada outlet Okeshop ITC Roxy Mas, Jakarta Pusat) - Wibowo, Setyo Ferry; Kurnaen, Teguh; Kresnamurti R. P., Agung (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purpose of the research are: to know the description of product attributes, variety seeking, and brand switching decision of handphone Nokia to Samsung Smartphone, test empirically the influence of product attributes toward brand switching decision of handphone Nokia to Samsung smartphone, test empirically the influence of variety seeking toward brand switching decision of handphone Nokia to Samsung smartphone, test empirically the influence of product attributes and variety seeking toward brand switching decision of handphone Nokia to Samsung smartphone. This is a quantitative research, descriptive and causal design, collecting data by survey method. Population of this research is visitors of Outlet Okeshop ITC Roxy mas, Central Jakarta who use Samsung smartphone and had use handphone Nokia before. Analysis of the research was conducted using SPSS. The results of the t test shows the product attributes and brand switching significantly influence the significance value, and variety seeking toward brand switching are also significantly influence. The results of F test simultaneously indicates product attributes and variety seeking influencing significantly to brand switching. And the result of determination analysis in this research shows the variation of variables product attributes and variety seeking could explained brand switching together. While the remainingare explained by other variables that are not included in this research model. Keywords: product attributes, variety seeking, brand switching